4(x+5)=-3(2x+10)

Simple and best practice solution for 4(x+5)=-3(2x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+5)=-3(2x+10) equation:


Simplifying
4(x + 5) = -3(2x + 10)

Reorder the terms:
4(5 + x) = -3(2x + 10)
(5 * 4 + x * 4) = -3(2x + 10)
(20 + 4x) = -3(2x + 10)

Reorder the terms:
20 + 4x = -3(10 + 2x)
20 + 4x = (10 * -3 + 2x * -3)
20 + 4x = (-30 + -6x)

Solving
20 + 4x = -30 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
20 + 4x + 6x = -30 + -6x + 6x

Combine like terms: 4x + 6x = 10x
20 + 10x = -30 + -6x + 6x

Combine like terms: -6x + 6x = 0
20 + 10x = -30 + 0
20 + 10x = -30

Add '-20' to each side of the equation.
20 + -20 + 10x = -30 + -20

Combine like terms: 20 + -20 = 0
0 + 10x = -30 + -20
10x = -30 + -20

Combine like terms: -30 + -20 = -50
10x = -50

Divide each side by '10'.
x = -5

Simplifying
x = -5

See similar equations:

| (7+9t)(-2)+3(-5+4k)= | | 100-24= | | 28x^3k^2w^2-36x^2k^4y+42x^3k^4-24x^2k^2yw^2=0 | | 2x^3+4x^2-18x-16=0 | | -83=7x+4(2x+13) | | 16(x-16)=512 | | 7n+2=4(n+1) | | 2x^4+3x^3-6x^2-6x+4=0 | | -2x+5(4x+4)=128 | | 3(x+4)=3x+13 | | (3w+11)w=70 | | k-245=-184 | | r-5=-6 | | 2(x+2)=11 | | -6-4(x+7)=22 | | 6x+5x+3+7=7x+4+3x | | x^3=-16x | | 45x^2-24x+32=0 | | 4x-5x*2=33 | | 3(c-2)-3=-15 | | 4x+2=5y+1 | | -3x-x+3=-5 | | 10x+7.5y=420 | | 8x-17=5x+13 | | h=-36t^2+gt+d | | y-8=-6(x+1) | | 4eX=20 | | 7x+2y+4=9+11y-x | | 5*4+20= | | -15=y+82 | | 4x^2-19x-52=0 | | -9=w-13 |

Equations solver categories